2007
DOI: 10.1002/dvdy.21371
|View full text |Cite
|
Sign up to set email alerts
|

Gastrulation in the spider Zygiella x‐notata involves three distinct phases of cell internalization

Abstract: The cell movements of gastrulation were analyzed in embryos of the spider Zygiella x-notata, using timelapse video, cell tracing, and improved histology. Cells are internalized near the center of the germ disc in three distinct phases. First, cumulus mesenchyme cells ingress and migrate as a group beneath the superficial layer. Second, mass internalization through a blastopore yields a diffusely organized deep layer. Third, superficial cells accumulate at the center of the germ disc to form the caudal bud. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…They migrate radially along the entire distance from the centre to the edge of the equator (comparable to the rim of the germ disc; Wolff and Hilbrant 2011). Our results support earlier findings (Akiyama- Oda and Oda 2003;Yamazaki et al 2005;Kanayama et al 2010) and correct the view that P. tepidariorum shows a canonical mode of gastrulation (Anderson 1973;Chaw et al 2007). …”
Section: Gastrulation and Origin Of Mesodermal Cellssupporting
confidence: 95%
See 1 more Smart Citation
“…They migrate radially along the entire distance from the centre to the edge of the equator (comparable to the rim of the germ disc; Wolff and Hilbrant 2011). Our results support earlier findings (Akiyama- Oda and Oda 2003;Yamazaki et al 2005;Kanayama et al 2010) and correct the view that P. tepidariorum shows a canonical mode of gastrulation (Anderson 1973;Chaw et al 2007). …”
Section: Gastrulation and Origin Of Mesodermal Cellssupporting
confidence: 95%
“…In addition to previous studies focusing mainly on behaviour, physiology and neuronal aspects of spiders (i.e. Melchers 1963;Seitz 1966;Weygoldt 1985;Miyashita 1987a, b;Kim and Roland 2000;Barth 2002;Stollewerk 2002;Morewood et al 2003;Hajer and Hrubá 2007;Weihmann et al 2010;Doeffinger et al 2010) and several dealing with chelicerate development (Yoshikura 1955(Yoshikura , 1958Crome 1963Crome , 1964Chaw et al 2007;Weygoldt 1965Weygoldt , 1975Weygoldt , 1979etc. ), chelicerates have become increasingly valued for comparative studies dealing with arthropod relationships and arthropod evolution during recent decades.…”
Section: Introductionmentioning
confidence: 96%
“…861405, Sigma-Aldrich; 1 mg ml 21 in PBS) was applied for 15 min. (Sekiguchi 1973;Chaw et al 2007;McGregor et al 2008). Transplantation or removal of the cumulus results in duplication or complete loss of the dorsal embryonic region (Holm 1952), while a gene expression study has revealed that the cumulus functions as an organizer that determines the dorsal region via decapentaplegic signalling (Akiyama-Oda & Oda 2003).…”
Section: Methodsmentioning
confidence: 99%
“…With multiple cell layers underneath the blastoderm (now ectoderm) this area represents the mesendodermal mass (mesodermal and endodermal cells). In many spider species, the formation and subsequent differentiation of the blastopore takes place at the centre of a structure called a germ disc [31,32]. This is a regional differentiation of blastodermic cells that migrate together, aggregating in the form of a disc.…”
Section: Introductionmentioning
confidence: 99%